2008
DOI: 10.1099/vir.0.83614-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional slippage prompts recoding in alternate reading frames in the hepatitis C virus (HCV) core sequence from strain HCV-1

Abstract: Since the first report of frameshifting in HCV-1, its sequence has been the paradigm for examining the mechanism that directs alternative translation of the hepatitis C virus (HCV) genome. The region encoding the core protein from this strain contains a cluster of 10 adenines at codons 8-11, which is thought to direct programmed ribosomal frameshifting (PRF), but formal evidence for this process has not been established unequivocally. To identify the mechanisms of frameshifting, this study used a bicistronic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
27
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
0
27
1
Order By: Relevance
“…Additional observations of transcriptional slippage on homopolymeric tracts have been reported in bacteriophages (10), prokaryotes (11)(12)(13)(14), viruses (15), and eukaryotes (16,17). A clear demonstration of in vivo transcriptional slippage during elongation was provided by Wagner et al (18), who showed that Escherichia coli RNA polymerase made slippage RNA products from templates with a homopolymeric tract greater than 9 nucleotides.…”
mentioning
confidence: 84%
“…Additional observations of transcriptional slippage on homopolymeric tracts have been reported in bacteriophages (10), prokaryotes (11)(12)(13)(14), viruses (15), and eukaryotes (16,17). A clear demonstration of in vivo transcriptional slippage during elongation was provided by Wagner et al (18), who showed that Escherichia coli RNA polymerase made slippage RNA products from templates with a homopolymeric tract greater than 9 nucleotides.…”
mentioning
confidence: 84%
“…In the case of viruses, polymerase slippage results in the alteration of newly synthesized RNA. The mechanism has been well characterized in animal RNA viruses such as Ebolavirus (1) (EBOV) or Hepatitis C virus (HCV) (2). For plant viruses of the Potyviridae family, polymerase slippage has been proposed as a general process of evolution (3), although a lack of experimental systems has precluded confirmatory data, and most pieces of evidence are indirect (4).…”
mentioning
confidence: 99%
“…*, P Ͻ 0.02 (Student's t test). 5=-GGCGTCTTCCCCAGATCTCCATCCTGCCCAGCC-3= coreϩ1 630 JFH1 5=-GGCGTCTTCCCCAGATCTGCCATCCTGCCCAGCC-3= core-1 630 JFH1 5=-GGCGTCTTCCCCAGATCTTCACCTGCCCAGCC-3= coreϩ1 630 H77 5=-GGCGTCTTCCCCAGATCTGCCATCCCGCCCACCC-3= N328 frameshift at codons 8 to 11 (7)(8)(9)33), internal initiation at codon 26 (12,15), a frameshift at codon 42 (16), and a shorter form initiating at codons 85/87 (13,15). As shown in Fig.…”
mentioning
confidence: 99%